Implementation of Sharia Compliance to Optimize Zakat Governance in the Frontier and Outermost Regions in Indonesia - Nurfahmi Islami Kaffah; Heru Susetyo (Universitas Negeri Semarang, 2020)
This research is a juridical and empirical study about the implementation of sharia compliance based on Law no. 23 the year 2011 on the Management of Zakat. BAZNAS, as the zakat management authority under the government, must implement good governance based on Islamic Sharia principles, trustworthiness, benefit, justice, legal certainty, integrated and accountability as a mandate from the zakat regulation. Sharia compliance is the main aspect in the management of zakat which consists the rules and the principles of sharia are essentially listed in the Qur’an, Hadith and developed in zakat fiqh related to principles of collecting and management of zakat, such as subject dan object of zakat, nisab and haul and the utilization and empowerment of zakat property. This study discusses the regulatory aspects of sharia compliance in the management of zakat, sharia principle in the operation of zakat, the stakeholders, indicators, reporting and auditing systems, and the benefits of implementing sharia compliance in zakat management. The research field was conducted in six ProvinceS in Indonesia (Aceh, West Nusa Tenggara, East Kalimantan Province, East Nusa Tenggara, North Sulawesi, Gorontalo). The implementation of sharia compliance in zakat institutions began to be effective in 2018 after the Decree of the Ministry of Religious Affairs Number 733 in 2018 concerning sharia audit guidelines for zakat management reports. The implementation of sharia compliance has a positive correlation with the implementation of good governance in the management of zakat institutions because it is associated with increased accountability and responsibility of zakat institutions. Sharia compliance is a strategic issue in achieving best practices in the management of zakat institutions, especially in ensuring legal certainty and trust in the community to optimize the empowerment of zakat in Indonesia.